2022
DOI: 10.3389/fphar.2022.990476
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rc ameliorated atherosclerosis via regulating gut microbiota and fecal metabolites

Abstract: Atherosclerosis (AS) and the accompanied cardiovascular diseases (CVDs) were the leading cause of death worldwide. Recently, the association between CVDs, gut microbiota, and metabolites had aroused increasing attention. In the study, we headed our investigation into the underlying mechanism of ginsenoside Rc (GRc), an active ingredient of ginsenosides used for the treatment of CVDs, in apolipoprotein E-deficient (ApoE −/− ) mice with high-fat diet (HFD). Sevenweek-old male ApoE −/− mice were randomly divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 61 publications
2
21
0
Order By: Relevance
“…Additionally, HFD-induced obesity reduces Ileibacterium spp., and the abundance of these bacteria is negatively correlated with chronic in ammatory diseases such as obesity, atherosclerosis, and aging [40][41][42]. It has been reported that Helicobacter negatively correlates with intestinal tight junction protein expression, which increases after HFD feeding [43].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, HFD-induced obesity reduces Ileibacterium spp., and the abundance of these bacteria is negatively correlated with chronic in ammatory diseases such as obesity, atherosclerosis, and aging [40][41][42]. It has been reported that Helicobacter negatively correlates with intestinal tight junction protein expression, which increases after HFD feeding [43].…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified the biomarkers of intestinal microbiota, which included included g__norank_f__Eubacterium_coprostanoligenes_group as a potential predictor for hair coat status. The effects of this genus may involve the reduction of cholesterol ( Freier et al, 1994 ), lipid and bile acid metabolism ( Xie et al, 2022 ), maintenance of colonic mucus barrier function, and decreased systemic inflammation ( Bai et al, 2021 ; Yang et al, 2021 ). Interestingly, this beneficial genus has also been reported to be enriched in fecal samples from high-productivity sows, compared to their low-productivity counterparts during late pregnancy ( Shao et al, 2019 ), as well as in the rumen of high-yield cows receiving the same diet ( Tong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes have the ability to positively modulate the host immune system, play an immunomodulatory role, defend against pathogenic microbes, and maintain normal physiological functions (20). Studies have indicated that treatment targeting gut microbes can delay the progression of coronary lesions (21). Although there have been meta-analyses on the effects of probiotics on lipid metabolism, glucose metabolism, blood pressure, and inflammatory factors (22,23), they do not consider the effects of conventional drugs on the intestinal flora (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%